2018
DOI: 10.1158/0008-5472.can-18-0161
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Mediate Synergistic Antitumor Effects of Combined Inhibition of HDAC6 and BET in a SCLC Preclinical Model

Abstract: Small-cell lung cancer (SCLC) has the highest malignancy among all lung cancers, exhibiting aggressive growth and early metastasis to distant sites. For 30 years, treatment options for SCLC have been limited to chemotherapy, warranting the need for more effective treatments. Frequent inactivation of TP53 and RB1 as well as histone dysmodifications in SCLC suggest that transcriptional and epigenetic regulations play a major role in SCLC disease evolution. Here we performed a synthetic lethal screen using the BE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 44 publications
1
34
0
1
Order By: Relevance
“…An HDAC inhibitor suppressed cell proliferation, induced cell cycle arrest and activated Notch signaling in SCLCs in vitro (34). Inhibitor of HDAC6, a cytoplasmic HDAC was shown in a prior study to cause NK cell dependent cytotoxicity in a preclinical SCLC model though the phenotype was not related to NKG2DLs (35).…”
Section: Discussionmentioning
confidence: 98%
“…An HDAC inhibitor suppressed cell proliferation, induced cell cycle arrest and activated Notch signaling in SCLCs in vitro (34). Inhibitor of HDAC6, a cytoplasmic HDAC was shown in a prior study to cause NK cell dependent cytotoxicity in a preclinical SCLC model though the phenotype was not related to NKG2DLs (35).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, our results demonstrating the remarkable efficacy of the combination of PD-L1 blockade with PARP or CHK1 inhibition provide a strong scientific rationale for combining these modalities in clinical trials for patients with SCLC. Further studies will be necessary to carefully interrogate the contribution, if any, of the neoantigen load and other immune cell populations, such as natural killer cells (43), during DDR-mediated T-cell activation. Because prexasertib, olaparib, and other PARP inhibitors are already in clinical trials for SCLC, we expect that these findings have the potential for rapid translation into the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, selective HDAC6 Inhibitor ACY-1215 and/or BET inhibitor JQ1, as well as vehicle control, were applied to athymic nude mice carrying human small cell lung cancer (SCLC) NCI-H69 xenograft tumors. A gene expression heat map was generated from RNA-seq analysis of these xenograft tumors, which showed that ACY-1215 treatment had limited change with transcription profiling as compared to JQ1 treatment [54].…”
Section: Transcriptomic Effects Of Hdismentioning
confidence: 99%